High crustal diversity preserved in the lunar meteorite Mount DeWitt 12007 (Victoria Land, Antarctica). (8th January 2016) - Collareta, Alberto; D'Orazio, Massimo; Gemelli, Maurizio; Pack, Andreas; Folco, Luigi
Abstract: The meteorite Mount DeWitt (DEW) 12007 is a polymict regolith breccia mainly consisting of glassy impact‐melt breccia particles, gabbroic clasts, feldspathic clasts, impact and volcanic glass beads, basaltic clasts, and mingled breccia clasts embedded in a matrix dominated by fine‐grained crystals; vesicular glassy veins and rare agglutinates are also present. Main minerals are plagioclase (typically An>85 ) and clinopyroxene (pigeonites and augites, sometimes interspersed). The presence of tranquillityite, coupled with the petrophysical data, the O‐isotope data (Δ 17 O = −0.075), and the FeOtot /MnO ratios in olivine (91), pyroxene (65), and bulk rock (77) indicate a lunar origin for DEW 12007. Impactites consist of Al‐rich impact‐melt splashes and plagioclase‐rich meta‐melt clasts. The volcanic products belong to the very low titanium (VLT) or low titanium (LT) suites; an unusual subophitic fragment could be cryptomare‐related. Gabbroic clasts could represent part of a shallow intrusion within a volcanic complex with prevailing VLT affinity. DEW 12007 has a mingled bulk composition with relatively high incompatible element abundances and shows a high crustal diversity comprising clasts from the Moon's major terranes and rare lithologies. First‐order petrographic and chemical features suggest that DEW 12007 could be launch‐paired with other meteorites including Y 793274/981031, QUE 94281, EET 87521/96008, and NWA 4884.